Polyhydroxyalkanoates (PHA) production from fermented crude glycerol: Study on the conversion of 1, 3-propanediol to PHA in mixed microbial consortia. (1st January 2018) - Burniol-Figols, Anna; Varrone, Cristiano; Daugaard, Anders Egede; Le, Simone Balzer; Skiadas, Ioannis V.; Gavala, Hariklia N.
Abstract: Crude glycerol, a by-product from the biodiesel industry, can be converted by mixed microbial consortia into 1, 3-propanediol (1, 3-PDO) and volatile fatty acids. In this study, further conversion of these main products into polyhydroxyalkanoates (PHA) was investigated with the focus on 1, 3-PDO. Two different approaches for the enrichment of PHA accumulating microbial consortia using an aerobic dynamic feeding strategy were applied. With the first approach, where nitrogen was present during the whole cycle, no net production of PHA from 1, 3-PDO was observed in the fermented effluent, not even in a nitrogen-limited PHA accumulation assay. Nevertheless, experiments in synthetic substrates revealed that the conversion of 1, 3-PDO to PHA was possible under nitrogen limiting conditions. Thus, a different enrichment strategy was formulated where nitrogen was limited during the feast phase to stimulate the storage response. Nitrogen was still supplied during the famine phase. With the latter strategy, a net production of PHA from 1, 3-PDO was observed at a yield of 0.24 Cmol PHA/Cmol 1, 3-PDO. The overall yield from the fermented effluent was 0.42 Cmol PHA/Cmol substrate. Overall, the PHA yield from 1, 3-PDO seemed to be limited, similarly to when using glycerol as a substrate, by a decarboxylation step and accumulation of other storage polymers such as glycogen, and possibly, lipid inclusions. Graphical abstract: Image 1 Highlights: Nitrogen had a critical role in the conversion of 1, 3-propanediol (1, 3-PDO) to PHA. An enrichment with nitrogen limitation during the feast phase was proposed. The PHA yield from 1, 3-PDO was 0.24 Cmol PHA/Cmol substrate. The PHA yield from 1, 3-PDO was limited by the synthesis of other storage compounds.